Use of multispectral satellite data to assess impacts of land management practices on wetlands in the Limpopo Transfrontier River Basin, South Africa. Issue 2 (3rd April 2022) - Dzurume, Tatenda; Dube, Timothy; Thamaga, Kgabo Humphrey; Shoko, Cletah; Mazvimavi, Dominic
ABSTRACT: The study sought to assess the impacts of land use and land cover (LULC) changes on two wetland systems (Makuleke and Nylsvley Nature Reserve) in the Limpopo Transfrontier River Basin (LTRB) in South Africa between 2014 and 2018. To fulfil this objective, multi-date Landsat images were used. Furthermore, the maximum likelihood classification algorithm was used to identify various LULC classes within delineated wetlands. The LULC changes were mapped from the two wetlands, with high overall accuracies,  ranging from 80% to 89% for both study areas. The spatial extent of the Makuleke wetland declined by 2% between 2014 and 2018, whereas the Nylsvley wetland decreased by 3%. Built-up areas have increased slightly over the 2014 and 2018 period because of population growth and infrastructure development, which occupy a portion of the wetland. In Nylsvley wetland, it was evident that during the 5-year monitoring period, croplands increased steadily in the Nylsvley catchment. Overall, the results demonstrated a steady decline in natural vegetation cover in both wetlands. This information can aid in enforcing wetland legislations and LULC management practices that can help protect them from further encroachment and degradation.